Ethanol synthesis from glycerol by Escherichia coli redox mutants expressing adhE from Leuconostoc mesenteroides - Nikel, P.I. (2010)
Aims: Analysis of the physiology and metabolism of Escherichia coli arcA and creC mutants expressing a bifunctional alcohol-acetaldehyde dehydrogenase from Leuconostoc mesenteroides growing on glycerol under oxygen-restricted conditions. The effect of an ldhA mutation and different growth medium modifications was also assessed. Methods and Results: Expression of adhE in E. coli CT1061 [arcA creC(Con)] resulted in a 1·4-fold enhancement in ethanol synthesis. Significant amounts of lactate were produced during micro-oxic cultures and strain CT1061LE, in which fermentative lactate dehydrogenase was deleted, produced up to 6·5 ± 0·3 g l-1 ethanol in 48 h. Escherichia coli CT1061LE derivatives resistant to >25 g l-1 ethanol were obtained by metabolic evolution. Pyruvate and acetaldehyde addition significantly increased both biomass and ethanol concentrations, probably by overcoming acetyl-coenzyme A (CoA) shortage. Yeast extract also promoted growth and ethanol synthesis, and this positive effect was mainly attributable to its vitamin content. Two-stage bioreactor cultures were conducted in a minimal medium containing 100 μg l-1 calcium d-pantothenate to evaluate oxic acetyl-CoA synthesis followed by a switch into fermentative conditions. Ethanol reached 15·4 ± 0·9 g l-1 with a volumetric productivity of 0·34 ± 0·02 g l-1 h-1. Conclusions: Escherichia coli responded to adhE over-expression by funnelling carbon and reducing equivalents into a highly reduced metabolite, ethanol. Acetyl-CoA played a key role in micro-oxic ethanol synthesis and growth. Significance and Impact of the Study: Insight into the micro-oxic metabolism of E. coli growing on glycerol is essential for the development of efficient industrial processes for reduced biochemicals production from this substrate, with special relevance to biofuels synthesis. © 2010 The Society for Applied Microbiology.